Causas das quedas expressivas da bolsa de valores brasileira entre 1994 e 2021 - Pressi, Junior Malinoski (2022)
The very sharp falls of the Stock Exchange are a terror for any investor and, due to the high volatility of the stock market, they have happened several times in history. Therefore, the present study sought to analyze the main factors that influenced the significant declines of the Brazilian Stock Exchange between 1994 and 2021. Eight declines from 1994 to 2021 were analyzed, referring to the Mexican Crisis in 1994, the Asian Tiger Crisis in 1997, the Russian Moratorium in 1998, September 11 in 2001, Political Instability in 2002, Subprime in 2008, the Lost Decade in 2011 and Covid-19 in 2020. Among the results, declines ranging from 24, 30% to 49.59%, the highest in 2008, caused by the Subprime crisis, the latter being the biggest drop in the period and the one that required the most time for the market to recover, taking 111 months. The impacts on the economy were varied, from light impacts, almost non-existent, to repercussions that lasted for years, helping to generate other shocks in the future.